2022
DOI: 10.3390/ijms23031477
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific Endothelial Cell Differentiation and Impact of Microenvironmental Cues on Endothelial Heterogeneity

Abstract: Endothelial cells throughout the body are heterogeneous, and this is tightly linked to the specific functions of organs and tissues. Heterogeneity is already determined from development onwards and ranges from arterial/venous specification to microvascular fate determination in organ-specific differentiation. Acknowledging the different phenotypes of endothelial cells and the implications of this diversity is key for the development of more specialized tissue engineering and vascular repair approaches. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 200 publications
(283 reference statements)
0
26
0
Order By: Relevance
“…Metastatic lesions with higher responses were typically found in the liver, spleen, LN, and lungs. These organs have discontinuous or fenestrated endothelial membranes, which may lead to higher drug exposure, potentially conferring high treatment responses 47,48 . In contrast, the organs bearing poorly-responding lesions are usually those with continuous endothelial membranes and thus more limited drug distribution, such as the muscle and brain/CNS [49][50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic lesions with higher responses were typically found in the liver, spleen, LN, and lungs. These organs have discontinuous or fenestrated endothelial membranes, which may lead to higher drug exposure, potentially conferring high treatment responses 47,48 . In contrast, the organs bearing poorly-responding lesions are usually those with continuous endothelial membranes and thus more limited drug distribution, such as the muscle and brain/CNS [49][50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to endothelial tissue located in other regions of the human body, the brain endothelium is characterized by a higher selectivity, one of the most important features of the BBB in brain protection [ 28 ]. The most relevant particularities of this highly specialized endothelium are the lack of fenestration, the reduced transcellular transport via minimal pinocytosis, and the complex intercellular connections [ 29 ]. Indeed, the almost absent paracellular diffusion is a result of the presence of tight junctions (TJs) and adherens junctions (AJs) that connect two neighboring BMECs [ 30 ].…”
Section: The Structure and Function Of The Blood–brain Barrier In Phy...mentioning
confidence: 99%
“…Presenter cell modification in the clinical hypothesis above explains why there is a conflict with the conclusions of an in vitro study, showing that the spike protein does not share tissue homology with myocarditis-associated antigens [ 33 ]. Numerous studies have demonstrated a slight increase in myocardial reactions and myocarditis, post vaccination—especially in young men [ 34 , 35 ]—and antigen modification of cardiac endothelial presenter cells [ 36 ] would invalidate that conclusion, and furthermore suggest that such modification is key to the damage done by SARS-CoV-2 and its antigens. The latter article argues that the protective benefit of the vaccine is greater than the slight risk of damage.…”
Section: Cross-reactive Attackmentioning
confidence: 99%